DEVELOPMENT OF DIGITAL LITERACY AND PROBLEM-SOLVING SKILL-INFUSED ENGLISH READING MATERIALS FOR SENIOR HIGH SCHOOL STUDENTS. A NEED ANALYSIS - Hapizah, Siti Nurul; Sulistyaningrum, Siti Drivoka (Journal of English Educational Study (JEES), 2024)
This study aims to analyze the English reading materials currently used by senior high school students and evaluate the extent to which they incorporate digital literacy and problem solving. The study was conducted at a senior high school in Bekasi, Indonesia. The research employs qualitative content analysis to examine the existing English reading materials, which consist of English textbooks. Furthermore, interviews with three English teachers were conducted to explore the needs of learning materials further. The findings reveal a gap between the current materials and the descriptors of digital literacy and problem solving. Therefore, it indicates an urgency to develop new English reading materials that promote problem solving and incorporate digital literacy to better facilitate the students’ needs.